Exploring University Students' Perceptions of AI: Insights from Indonesia - Irpan Apandi Batubara; Wariyati Wariyati; Yugi Diraga Prawiyata (ITScience (Information Technology and Science), 2024)
Artificial Intelligence (AI) is transforming education massively. As AI increasingly integrates into a learning environment, understanding students' opinions is crucial for optimizing its usage in higher education contexts. This study explores the perceptions and experiences of first-semester university students in Indonesia regarding artificial intelligence within the context of higher education. This research investigates students' views on their motivation to use AI and its perceived advantages and disadvantages. Through a case study approach, this study used semi-structured interviews with 50 first-semester students at a private university In Indonesia. The study reveals a complex insight. This study uncovers students' experience trying AI for their learning and their enthusiasm for re-using it. This study also uncovers students' motivation to use AI. Students recognize AI's potential to enhance learning, simplify academic tasks, and foster lifelong learning. However, they also express concerns about AI's accuracy, the potential for diminished critical thinking skills, ethical implications, and accessibility issues. The findings underscore the need for comprehensive AI literacy education in Indonesian universities, emphasizing technical skills, ethical considerations, critical thinking, and responsible AI usage. Moreover, this contributes to the growing body of knowledge on AI in education and provides valuable insights for educators and policymakers seeking to integrate AI into higher education in Indonesia effectively.